2017
DOI: 10.4172/neuropsychiatry.1000s1007
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of Refractory Epilepsy and the Update Mechanism

Abstract: Epilepsy is still an issue that perplexes the epileptologists worldwide, with a reported impact on 50 million populations. With the reconceptualization of epilepsy as a disease of brain networks, it is great timing to rethink epilepsy and those associated comorbidities, including cognitive and behavioral comorbidities, psychiatric comorbidities, cardiovascular disease and migraine. In this review, we introduce the state of the art of these comorbidities of refractory epilepsy, including etiology, epidemiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…This is evidenced by transgenic overexpression of ADK in the brain of mice (Adk-tg mice) caused prominent cognitive impairment on several levels [31,32]. In clinical practice, cognitive deficits, or mental retardation, may be considered as one of most common comorbidities of refractory epilepsy, especially for children [3,33]. Our recent study has demonstrated that vagus nerve stimulation (VNS) or deep brain stimulation (DBS) might improve neuropsychological outcomes, including language, memory, perception [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by transgenic overexpression of ADK in the brain of mice (Adk-tg mice) caused prominent cognitive impairment on several levels [31,32]. In clinical practice, cognitive deficits, or mental retardation, may be considered as one of most common comorbidities of refractory epilepsy, especially for children [3,33]. Our recent study has demonstrated that vagus nerve stimulation (VNS) or deep brain stimulation (DBS) might improve neuropsychological outcomes, including language, memory, perception [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The term "co morbidity" refers to one or more other disease among people with an index disease 6 .With the reconceptualization of epilepsy as a disease of brain network, it is great timing to rethink epilepsy and those associated comorbidities, including cognitive and behavioral co morbidities, psychiatric co morbidities, cardiovascular disease and migraines 1 .The epilepsy associated co morbidities are often underestimated, consequently, undertreated. Furthermore, cognitive deficits always remain despite seizure greatly control 7 .…”
Section: Original Article Open Accessmentioning
confidence: 99%
“…Epilepsy is still an issue that perplexes the epileptologists worldwide, with a reported impact on 50 million populations 1 . Seizures affect 4-7% of children 2 .…”
Section: Introductionmentioning
confidence: 99%